Humanizing Smart Cities: A Preconception to a Better Life for All - Shehayeb, Dina; Tawfik, Mennatallah; ElSayed, Mirame; Emad, Shaimaa; Halawa, Esraa (2023 2nd International Conference on Smart Cities 4.0, 2023)
As cities face the challenge of conceiving new and more competitive and sustainable development models, there has been an emergence of introducing technology to cities to enhance the quality of life it provides to the citizens. The "Smart City" was proposed as a new prototype of technology-based urban development. These smart cities witness the emergence of the metaverse and platform societies, machine learning and artificial intelligence (ML/AI), big data, the Internet of Things (IoT) systems, and many other innovative and advanced technologies. However, the idea of the Smart City has developed in such a form that cities have started to encounter the risks of losing social inclusiveness and connection with the human dimension. This research tries to tackle one of the main challenges of urbanism, which is shifting smart city development to be more humanized and people-centered. It also maps the broader approaches and perspectives while reviewing smart cities and addressing their challenges, contributing to the reconceptualization of the Smart City notion. This research also aims to introduce an integrated conceptual framework shifting the experience of smart cities through humanizing the technology to be more human-compatible smart cities. This study tends to help the decision-makers and urban planners build upon the outcome of this research through further exploration of implementation processes toward humanizing future smart cities.